The effect of special force training on the development of biomechanical variables for running raising awareness during the performance on the jumping table - Razzaq, Z. A. S. A.; Almujamay, A. S.; Almojamay, H. A. M. (Journal of Human Sport & Exercise, 2019)
The strength training greatly affect the speed of motor performance, especially the stage of the performance of the raft and the upgrade, where the player needs to force the moment of elevation to pass the jump platform, and must be based on these exercises based on real indicators based on scientific results to know the nature of this power of the player and its impact on The length of the step of the glove during the moment of elevation to pass the plate of advancement, through sweating on the nature of the power of the initial hula the last three steps and hitting the plate of the advancement can be used (Foot scan) to determine this strength and corrected foot position and areas of pressure taken to develop this Thus enabling the effect of mechanical variables and achieving good performance of these skills. The researcher was keen to measure these forces through the use of a foot scanner and the extraction of kinematic variables for the skill of the Arab jump, especially the rough stage and the advancement through video photography and kinetic analysis and the preparation of special exercises to develop these variables in order to solve This problem was imposed by the researcher. There are no statistically significant differences between the tribal and remote tests in the indices of the foot scan and the kinetics and the strength of the Tsukahara skill of the Round Off Back tuck (Tsukahara) on the jumping platform. The research on the sample of the research on the players of the national junior team for the ages (11-13) years (6) players was extracted and the value of (T) between the results of tribal and remote tests and concluded the researcher. The effectiveness of the exercises in the training curriculum in the improvement of the rounder and upgrade according to the indices (Foot scan) and kinetic in the performance of the round off back tuck (Tsukahara) on the jump platform, and worked to reduce the deviation of the foot from the real path of the approximate run, which helps the economy time and effort and reduce Distance and skill development.